Geriatric health care in degenerative disorders – a public health initiative - Tomar, Sunita; Agrawal, Nivedita; Jaliya, Vishal K.; Tare, Garima (International Journal Of Community Medicine And Public Health, 2025)
Background: A project under public health initiative (PHI) scheme for geriatric health care in degenerative disorder of elderly in urban and rural area of Tehsil Huzur, Bhopal, Madhya Pradesh was conducted. The study explored geriatric problems with comorbidity among individuals. The survey form covers 33 items which were further sub-divided that capture the clinical variables, physical and cognitive status, medical diagnoses, major health problems and symptoms, current service use, medication use and overall health status. During the survey 50084 patient’s data were collected and after cleaning of data whose data is incomplete, this left a sample of 19740 patients. Methods: The retrospective cohort study was conducted. Result: The main characteristics of study sample, according to enrolment. The 10 most common chronic diseases observed in the study population in a decreasing frequency were knee joint pain (58.55%), cardiovascular diseases (51.26%), eye or vision related conditions or problems (46.59%), hypertension (38.16%), constipation (34.20%), back pain (33.33%), refractive error (33.31%), diabetes (27.60), sleep related problem (20.75%) and abdominal discomfort (18.56%). The knee joint pain (58.55%) was more prevalent in males (29.45%) than females (29.10). Conclusions: The age-related physiological deterioration of normal physical functioning is the source of many chronic health issues, such as poor mobility, vision, hearing, memory loss, difficulty eating and digesting food, and an inability to manage specific physiological systems. Integrating AYUSH treatments into conventional healthcare could enhance holistic approaches to addressing chronic illnesses in geriatric age group.